Dekonstruksi Kapitalisasi Dalam Komunikasi Digital Generasi Z - S, Sugiarti; Nurfaonah, Endang; Hasanah, Uswatun (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Language is the primary communication tool in daily life, also serving as a symbol of national identity and a custodian of culture. In Indonesia, the use of the Indonesian language is standardized through the General Guidelines for Indonesian Spelling (PUEBI), including capitalization rules. However, in the digital era, especially among Generation Z, there has been a shift in language practices due to the influence of social media. One prominent phenomenon is the trend of "typing cantik" or aesthetic typing, such as using all lowercase letters or all caps, which often disregards the correct capitalization rules. This study aims to describe and analyze capitalization errors in digital communication among Gen Z, focusing on messages sent via the WhatsApp platform. The method used is qualitative descriptive with data collection and error analysis techniques. The results show various violations of the PUEBI capitalization rules, such as writing people's names, sentence beginnings, and place names without capital letters.